Dinâmica de crescimento de gramíneas nativas do Rio Grande do Sul submetidas a dois intervalos entre pastoreios - Confortin, Anna Carolina Cerato (2012)
It was studied growth dynamics of Andropogon lateralis, Aristida laevis, Axonopus affinis, Paspalum notatum and Paspalum plicatulum in a natural grassland of the Depressão Central of Rio Grande do Sul, subjected to rotational grazing with heifers, in the spring and summer of 2010/2011. The experimental design was completely randomized with 5 x 2 factorial arrangements, with two grazing intervals, defined by thermal sums of 375 and 750 degree-days, and five species of grasses. Leaf tissue flows, tiller dynamics and stability index of plant population of these grasses were assessed. The studied grasses had a higher leaf growth flow and balance between flows when subjected to grazing intervals of 750 degreedays and higher real efficiency of utilization, tiller appearance rate and site filling when subjected to grazing intervals of 375 degree-days. A. lateralis showed the highest flows of leaf growth, intake and senescence. A. laevis exhibited the lowest real efficiency of utilization. A. affinis and P. notatum had the highest rates of appearance of tillers. P. plicatulum was the only species with stability index of less than one in mean of the period and who had decline in their population of plants. Evaluation periods and/ or seasons influenced the number of senescent leaves per tiller, leaf intake flow, rates of appearance, survival and mortality of tillers and tiller population stability. Summer and, especially the month of December, represented a period of reproductive development of grasses. Intervals between grazing defined in order to respect the natural rhythms of growth of the species tend to optimize the productivity of natural grasslands.